SAT0189 A NOVEL DEVICE FOR RAPID MINOR SALIVARY GLAND BIOPSY IN SUSPECTED SJÖGREN'S SYNDROME. (June 2019) - Dumusc, Alexandre; Bannert, Bettina; Dan, Diana; Huegle, Thomas
Abstract : Background: Labial minor salivary glands (MSG) biopsies are a frequently performed diagnostic procedure for Sjögren's syndrome. MSG biopsy usually requires additional assistance e.g. to provide lower lip protrusion and to apply pressure on the lip during the procedure. The latter is done to foster protrusion of salivary glands and therefore to reduce the incision depth and potential nerve damage. We recently developed a new single-use device for MSG by 3D-printing in form of a lip clamp with a stamp on the lower arm to reduce invasiveness and to facilitate the intervention. Objectives: To assess practicability and to describe the technical application of this device for MSG biopsies in the rheumatology department. Methods: Retrospective study of MSG biopsies performed with the use of a dedicated lip clamp. For each MSG biopsy, we recorded if any assistance was needed during the procedure, occurrence of any complication, if salivary glands were obtained and if the quality of the salivary gland tissue sample was adequate for histologic analysis. Results: 12 MSG biopsies performed on 12 patients with suspected Sjögren's syndrome were included in the study. MSG biopsies were performed between August 2018 and January 2019. Using the lip clamp, the physician was able to perform all the biopsies without assistance. No complication occurred with a follow-up of 1 week for each patient. Salivary glands tissue samples were obtained in 11/12 of the patients using 1 incision. For 1 patient, a second incision had to be performed on the contralateral side of the lip during the same intervention because no glands were found on the first attempt. Quality of all the samples was adequate for histologic analysis. We did not observe an increase in procedure time compared to routine MSG biopsy procedure. Conclusion: The use of a single-use lip clamp facilitates MSG biopsy without needing assistance and potentially reduces invasiveness and collateral damage. Quality of the tissue samples obtained was adequate for histological analysis. Disclosure of Interests: Alexandre Dumusc: None declared, Bettina Bannert: None declared, Diana Dan: None declared, Thomas Huegle Grant/research support from: AbbVie, Lilly, Novartis and Pfizer, Speakers bureau: AbbVie, Lilly, Novartis and Pfizer